Evaluasi Tata Kelola IT Resource Optimisation Berdasarkan Framework Cobit 5 Pada Dinas Komunikasi Dan Informasi Palembang - Agiyani, Gina; Cholil, Widya (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2024)
The Palembang Information and Communication Office is a government agency that leverages information technology to enhance its services. However, it faces several internal challenges that must be minimized to achieve good governance. These challenges include the rapid advancement of information technology, a shortage of human resources with expertise in communication and information, and insufficient employee numbers. To address these issues, optimizing IT resources is crucial. The Control Objectives for Information and Related Technology (COBIT) framework can serve as a reference to measure the effectiveness of IT usage at the Palembang Information and Communication Office. The IT services provided aim to support the Palembang Communication and Information Office in delivering efficient services to the public. For information technology to contribute effectively to organizational performance, its objectives must align with business goals. Therefore, evaluating IT governance using COBIT 5 is essential to improving service performance at the Palembang Information and Communication Office.